Spin crossover-induced colossal positive and negative thermal expansion in a nanoporous coordination framework material - Benjamin R. Mullaney; Laurence Goux-Capes; David J. Price; Guillaume Chastanet; Jean-François Létard; Cameron J. Kepert (Nature Communications, 2017)
Controlling mechanical motions in solid state devices is highly desirable for the development of nanoscale machines. Here, Kepert and colleagues exploit an ultra-flexible coordination framework in which thermally-controlled Fe(II) spin transitions result in remarkable flexing of the crystal lattice.